Macrophage-mimetic liposomes co-delivering ceria and Ac2-26 peptide for penumbra protection in ischemic stroke - Lingyun Bai; Na Li; Huiqin Li; Yuxuan Dai; Yi Bai; Feiyu Ma; Dujuan Sha; Shengnan Xia; Yun Xu; Xiang Cao (Journal of Nanobiotechnology)
Abstract Ischemic stroke is one of the most severe central nervous system disease with high disability and mortality rates worldwide. Effective treatment requires strategies that address the multifaceted pathophysiology of ischemic penumbra, including oxidative stress-induced neuronal apoptosis and blood-brain barrier (BBB) disruption. Here, inspired by the inflammation-homing property of macrophages, we developed macrophage-mimetic liposomes (MM-LPs) by integrating macrophage membranes with liposomes for the co-delivery of cerium oxide nanoparticles (CeO2) and the Ac2-26 peptide (CeO2-Ac2-26@MM-LPs). CeO2 effectively scavenged reactive oxygen species (ROS), improving mitochondrial function and inhibiting neuronal apoptosis, while Ac2-26 upregulated tight junction proteins to enhance BBB integrity. In a transient middle cerebral artery occlusion (tMCAO) mouse model, CeO2-Ac2-26@MM-LPs exhibited significant accumulation in ischemic regions, where they exerted dual protective effects on the ischemic penumbra by mitigating neuronal damage and preserving BBB integrity. This resulted in improved neurological function, reduced infarct volume, and attenuated BBB disruption. Mechanistically, CeO2-Ac2-26@MM-LPs activated the NRF2 signaling pathway, upregulating antioxidant enzymes (HO-1 and NQO1), while simultaneously suppressing NF-κB activation, thereby reducing neuronal death and BBB damage in the penumbra. This multi-target combination strategy provides a promising platform for ischemic stroke treatment, with potential applicability to other neurological disorders characterized by oxidative stress and BBB disruption.